ОСНОВНЫЕ ПРИНЦИПЫ И ФУНКЦИИ СТРАТЕГИЧЕСКОГО И ФУНКЦИОНАЛЬНОГО МЕНЕДЖМЕНТА ОБРАЗОВАНИЯ - Магрупов, А.М. (SCIENCE and SOCIETY, 2017)
The article presents the basic principles and functions of the two types of innovation management - functional and strategic. Innovation management performs certain functions that determine the formation of the control structure of the system of educational institutions in the implementation of the innovation process.